2015
DOI: 10.3945/jn.115.216382
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Energy Malnutrition Causes Deficits in Motor Function in Adult Male Rats

Abstract: PEM in adult male rats causes a variety of sensorimotor abnormalities that develop at different stages of malnutrition. This model can be used in combination with disease models of sensorimotor deficits to examine the interactions between nutritional status, other treatments, and disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…The loss of muscle mass and decreased cross‐sectional area in the plantaris muscle were observed in the malnutrition group, but no atrophy was observed in the soleus muscle. Several previous studies reported that excessive dietary restriction or ingestion of a low‐protein diet results in loss of muscle mass in fast muscles (Kim, 2013; Pereyra‐Venegas et al, 2015; Ruiz‐Rosado et al, 2013; Toyoshima et al, 2014) and no atrophy was induced in slow muscles (Alaverdashvili et al, 2015; Salles et al, 2014; Walrand et al, 2000). In addition, Sakaida et al, (1987) reported that glycogen content in muscle fibers decreased predominantly in type IIB fibers after 2 days of starvation and almost disappeared after 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of muscle mass and decreased cross‐sectional area in the plantaris muscle were observed in the malnutrition group, but no atrophy was observed in the soleus muscle. Several previous studies reported that excessive dietary restriction or ingestion of a low‐protein diet results in loss of muscle mass in fast muscles (Kim, 2013; Pereyra‐Venegas et al, 2015; Ruiz‐Rosado et al, 2013; Toyoshima et al, 2014) and no atrophy was induced in slow muscles (Alaverdashvili et al, 2015; Salles et al, 2014; Walrand et al, 2000). In addition, Sakaida et al, (1987) reported that glycogen content in muscle fibers decreased predominantly in type IIB fibers after 2 days of starvation and almost disappeared after 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in animal models of focal cerebral ischemia found that undernutrition reduces brain injury [7-9, 16, 17], whereas other studies in models of focal or global ischemia showed that ischemic injury was unchanged by undernutrition [10][11][12][13]. A variety of studies in models of focal or global ischemia observed a significant reduction of stroke-induced neurological deficits [7][8][9][10][11], whereas other studies, again in focal or global ischemia, noted exacerbated or unchanged deficits [12][13][14][15]. Major differences in these studies relate to the type of undernutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Major differences in these studies relate to the type of undernutrition. As such, undernutrition was induced by (a) reducing food access to 60 or 70% of the average amount of control animals for 4 weeks to 3 months [8,10,13,16], (b) reducing food protein content to 0 to 12% for 6 days to 4 weeks [9,12,14,15], or (c) intermittent fasting on alternate days or twice per week for one to several months [7,11,17]. While reducing the amount of food access similarly reduces protein and energy consumption, the reduction of protein content to 0-2% results in a reduction in the total amount of food ingested, since the animals refuse this chow [9,12,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 These effects of PEM on cardiac function caused by muscle atrophy are due to inadequate protein and cardiovascular energy or indirectly due to metabolic disorders and increased systemic demand. 24…”
Section: Discussionmentioning
confidence: 99%